Research on the Vibration Characteristics of a Compounded Periodic Strut Used for Helicopter Cabin Noise Reduction. (3rd October 2017) - Lu, Yang; Wang, Fengjiao; Ma, Xunjun
Abstract : A special periodic strut is developed to reduce the helicopter cabin noise in this paper. The strut exhibits unique dynamic characteristics which can isolate the gearbox vibrations from transferring to the fuselage and radiating noise. Modeling, simulation, and experimental research are carried out to explore its characteristics and performance. A theoretical model of the strut is firstly established, with particular emphasis on correlating the passband and stop band behaviors with the damping and a series of boundary conditions. Then, through simulations, it is shown that both the damping and boundary conditions have significant influences on the stop band, including the beginning and end frequencies and attenuation effects. Based on these analytical simulations, experimental analyses are conducted with the newly developed strut. Inspiring performances are validated under different conditions. Considering that the helicopter vibration in practical applications is much more complex, further experimental investigations are carried out on a helicopter model, which generates prominent gear mesh tones similar to a real helicopter. The experimental results show that the compounded periodic strut can significantly attenuate the vibrations transmitted to the fuselage. Compared with the plain strut, attenuations in excess of 40 dB are measured in the frequency range from 300 to 2000 Hz.